The role of commercial banks in India's developing economy - Sharma, B. P. (New Delhi : S. Chand, 1974)
The principal object of the study is to make an objective evaluation of the institutional, functional and developmental activities of Indian commercial banks since 1951.
Essentially a revision of the author's thesis, University of Rajasthan, 1970.
Includes index.
Bibliography: p. [405]-406.
osc 18/05/2018
Loans
Keywords: Banks and banking; Credit